2022
DOI: 10.3389/fnbeh.2022.995614
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on transcranial magnetic stimulation for post-stroke dysphagia

Abstract: Dysphagia is one of the most common manifestations of stroke, which can affect as many as 50–81% of acute stroke patients. Despite the development of diverse treatment approaches, the precise mechanisms underlying therapeutic efficacy remain controversial. Earlier studies have revealed that the onset of dysphagia is associated with neurological damage. Neuroplasticity-based transcranial magnetic stimulation (TMS), a recently introduced technique, is widely used in the treatment of post-stroke dysphagia (PSD) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Of the 19 studies included in the analysis, eight SRs investigated the effectiveness of rTMS on post-stroke dysphagia rehabilitation (Liao et al, 2017;Papadopoulou et al, 2018;Yang et al, 2021;Li H. et al, 2022;Qiao et al, 2022;Wen et al, 2022;Xie et al, 2022a;Hsiao et al, 2023) and 11 investigated various therapeutic methods on the topic, including rTMS (Yang et al, 2015;Pisegna et al, 2016;Bath et al, 2018;Chiang et al, 2018;Cheng et al, 2021;Balcerak et al, 2022;Tan et al, 2022;Zhu and Gu, 2022;Banda et al, 2023). For the specific focus of this umbrella review, from the latter studies, only the information pertaining to the use of rTMS for the treatment of dysphagia post-stroke was analyzed.…”
Section: Characteristics Of the Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 studies included in the analysis, eight SRs investigated the effectiveness of rTMS on post-stroke dysphagia rehabilitation (Liao et al, 2017;Papadopoulou et al, 2018;Yang et al, 2021;Li H. et al, 2022;Qiao et al, 2022;Wen et al, 2022;Xie et al, 2022a;Hsiao et al, 2023) and 11 investigated various therapeutic methods on the topic, including rTMS (Yang et al, 2015;Pisegna et al, 2016;Bath et al, 2018;Chiang et al, 2018;Cheng et al, 2021;Balcerak et al, 2022;Tan et al, 2022;Zhu and Gu, 2022;Banda et al, 2023). For the specific focus of this umbrella review, from the latter studies, only the information pertaining to the use of rTMS for the treatment of dysphagia post-stroke was analyzed.…”
Section: Characteristics Of the Systematic Reviewsmentioning
confidence: 99%
“…Numerous studies have explored the use of rTMS intervention in post-stroke dysphagia that is either inhibitory (e.g., Kim et al, 2011 ; Lim et al, 2014 ) or excitatory (e.g., Park et al, 2013 ; Momosaki et al, 2014 ; Lee et al, 2015 ). However, there is no agreement with regards to the optimal stimulation site (i.e., affected, unaffected or both hemispheres) and stimulation parameters ( Jones et al, 2020 ; Li Y. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“… It inhibits apoptosis and inflammatory response of neuronal cells in the ischemic penumbra, promotes nerve regeneration, repairs the function and metabolism of neurons in the ischemic brain area, and improves the Chinese medicine evidence and neurological deficits in IS patients. He et al, 2019 , Li et al, 2023 , Su and Fan, 2013 , Zhang et al, 2022 , Zhang et al, 2022 , Zhang et al, 2022 , Zhang, Fan, Guo, & Song, 2022 …”
Section: Intervention Of Tcm In Convalescence Stage Of Ismentioning
confidence: 99%
“…Post-stroke depression (PSD) is one of the most common complications of stroke, with patients displaying neuropsychiatric symptoms such as depression, anxiety, and loss of interest ( Li et al, 2023 ). The presence of anxiety and depression also seriously impacts patients' quality of life, mental health, and functional recovery.…”
Section: Intervention Of Tcm In Post-stroke Complicationsmentioning
confidence: 99%
“…TMS is a non-invasive technique that can be used to stimulate specific brain tissues and affect the activity of local neurons by transmitting magnetic pulses from copper coils. The mechanism of TMS may be related to synaptogenesis or recombination as well as activation or inhibition of the activity of target cortical neurons, which leads to long-term synaptic potentiation or inhibition, thereby inducing changes in brain plasticity ( 25 , 26 ). Tang et al ( 27 ) found that TMS can change the density, loss rate, and formation rate of dendritic spines in adult and aged mice, in addition to changing the function of synaptic connections in the brain.…”
Section: Basic Principles and Classification Of Tmsmentioning
confidence: 99%